2013
DOI: 10.18632/oncotarget.1411
|View full text |Cite
|
Sign up to set email alerts
|

SERPINB3 protects from oxidative damage by chemotherapeutics through inhibition of mitochondrial respiratory complex I

Abstract: SERPINB3 (SB3) is a serine protease inhibitor overexpressed in several malignancies of epithelial origin, including primary liver cancer, where it inhibits apoptosis through poorly defined mechanisms. In the present study we analyze the effect of SB3 on hepatoma cell death elicited by a panel of chemotherapeutic agents. We report that SB3 shields cells from the toxicity of drugs with a pro-oxidant action such as doxorubicin, cisplatin and EM20-25. The rapid rise in ROS levels prompted by these compounds causes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
76
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(78 citation statements)
references
References 47 publications
1
76
0
1
Order By: Relevance
“…6D). On the other hand, when another cell-death stimulus such as etoposide, which acts independently of mitochondrial Ca 2+ overload toxicity (33,34), was applied to control and Mfn2-KD cells, no difference was found in the number of annexin-V + cells (Fig. 6C), strongly suggesting a causal relationship between Mfn2, ER-mitochondria Ca 2+ transfer, and celldeath sensitivity.…”
Section: Mfn2 Ablation Does Not Alter the Dynamics Of Er-mitochondriamentioning
confidence: 95%
“…6D). On the other hand, when another cell-death stimulus such as etoposide, which acts independently of mitochondrial Ca 2+ overload toxicity (33,34), was applied to control and Mfn2-KD cells, no difference was found in the number of annexin-V + cells (Fig. 6C), strongly suggesting a causal relationship between Mfn2, ER-mitochondria Ca 2+ transfer, and celldeath sensitivity.…”
Section: Mfn2 Ablation Does Not Alter the Dynamics Of Er-mitochondriamentioning
confidence: 95%
“…In response to UV irradiation, SERPINB3 protects cells through a directly inhibitory effect on mitogen-activated protein kinase (MAPK) family members JNK or p38 [85, 86]. SERPINB3 has also been found to localize to the mitochondrial inner membrane to interact with Complex I and suppress mitochondrial ROS generation [87]. …”
Section: Mechanisms Of Actionmentioning
confidence: 99%
“…As a protease inhibitor, SERPINB3 is able to inhibit cysteine proteases (cathepsins L, S, K and papain) [10], and in cancer cells it confers resistance to drug-induced apoptosis by inhibiting lysosomal cathepsin proteases [23]. However, under a variety of stress conditions SERPINB3 displays an anti-apoptotic function unrelated to its proteinase inhibition activity [24, 25]. Indeed, SERPINB3 protects cells from exposure to radiation through an inhibitory effect either on the MAP family of c-Jun terminal kinase (JNK) [19] and the interaction between SERPINB3 and JNK1 was also supported by the crystallographic study [26]; or with a decreased phosphorylation of the proapoptotic p38 mitogen-activated protein kinase on p38 [27].…”
Section: Proteinmentioning
confidence: 99%
“…In addition, recent results, reported that SERPINB3 protects from oxidative damage by chemotherapeutics through inhibition of mitochondrial respiratory complex I [25]. …”
Section: Proteinmentioning
confidence: 99%